Effectiveness of Banana Tree Sap Extract (Musa paradisiaca) on Collagen Density After Incision in Wistar Rats (Rattus novergicus) Infected with Staphylococcus aureus - Putu Sulistiawati Dewi; Setiawan; Tu Bagus Satria Pajajaran (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: wounds in the oral cavity are at high risk of infection because of the large number of normal flora in the oral cavity that can be opportunistic, one of which is Staphylococcus aureus. Wound care is crucial, particularly the use of medications or materials that can aid in accelerating wound healing. One of the plants that can be used to heal wounds is the banana tree sap. The objective of this study is to determine the effectiveness of banana tree sap extract on collagen density in wound healing of Wistar rats infected with Staphylococcus aureus bacteria. Materials and Methods: This study is a laboratory experimental study conducted in vivo with a post-test only control group design, using 24 rats divided into four groups. Namely, the negative control group, the group that was given the banana tree sap extract gel at concentrations of 30%, 40%, and 50%. The in vivo test involved creating an incision wound in Wistar rats and subsequently infecting them with Staphylococcus aureus bacteria. The wound was then treated with gel extract twice daily. On the 7th day, specimens were decapitated to observe collagen density. The research data were analyzed using one-way ANOVA, followed by the Games-Howell post hoc test. Results and Discussion: The administration of banana tree sap extract was effective in the wound healing process, as evidenced by an increase in collagen density in the treatment at all concentrations. The increase in collagen density is due to the banana tree sap extract gel containing active substances, namely flavonoids, saponins, tannins, and alkaloids, which have anti-inflammatory, antibacterial roles, ward off free radicals, and stimulate collagen formation. Conclusion: 50% concentration of banana tree sap extract gel was more effective in increasing collagen density in the incision wound of Wistar rats infected with Staphylococcus aureus than concentrations of 30% and 40%.